An effective trap for spotted lanternfly egg masses - Lewis, Phillip; Davila-Flores, Amanda; Wallis, Emily (Frontiers in Insect Science, 2023)
Spotted lanternfly (SLF) (Lycorma delicatula (White)), an invasive planthopper discovered in Pennsylvania, USA in 2014, continues to spread and is now present in 14 states with substantial infestations present in seven states. Population projections using adult SLF trapping or visual counts are not reliable due to the transient, migratory behavior of the adults which make population forecasts difficult. Another approach to population monitoring is utilization of the stationary egg mass stage, but counting small cryptic egg masses throughout the canopy of large trees in dense woodlots is arduous and prone to error. After several field seasons testing various trapping configurations and materials, we have identified an efficient, simple, low-cost trap termed a ‘lamp shade trap’ that is attached to the lower trunk area of an SLF host tree. SLF females readily enter the trap and lay eggs on the thin, flexible trap surface. A vertical trap orientation was superior, and the most productive woodlots yielded an average of 47 and 54 egg masses per trap, and several traps had over 100 egg masses. There were 1,943 egg masses tallied from 105 traps placed at six locations in two states. Egg mass counts in the area above and below the traps and on nearby control trees yielded very few egg masses in comparison. Selection of trees 15 to 20 cm in diameter for trap placement is most efficient, yielding good egg mass abundance while minimizing the amount of trap material used. The lamp shade trap has potential as an effective tool to identify SLF in new areas, gauge SLF population levels in woodlots and can also be used to collect and monitor egg masses for research purposes.